2020
DOI: 10.3390/hydrology8010002
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Mapping of Tile Drainage in Agricultural Fields Using Unmanned Aerial System (UAS)-Based Radiometric Thermal and Optical Sensors

Abstract: With the growing concerns of water quality related to tile drainage in agricultural lands, developing an efficient and cost-effective method of mapping tile drainage is essential. This research aimed to establish mapping of tile drainage systems in agricultural fields using optical and radiometric thermal sensors mounted on Unmanned Aerial System (UAS). The overarching hypothesis is that in a tile-drained land, spatial distribution of soil water content is affected by tile lines, therefore, contrasting soil te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…(2020) found that a light rain of 13 mm 5 days prior to image acquisition was the reason for the poor detection of tile lines on thermal images. A more recent study (Tilahun & Syoum, 2021), however, found that a thermal image collected in the afternoon of a day on which 16.8 mm of rain fell in the morning showed better contrast than an image collected after 2 days of 2.3 mm rain. Additionally, Allred et al.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…(2020) found that a light rain of 13 mm 5 days prior to image acquisition was the reason for the poor detection of tile lines on thermal images. A more recent study (Tilahun & Syoum, 2021), however, found that a thermal image collected in the afternoon of a day on which 16.8 mm of rain fell in the morning showed better contrast than an image collected after 2 days of 2.3 mm rain. Additionally, Allred et al.…”
Section: Methodsmentioning
confidence: 91%
“…Indiana, with approximately 50% artificially drained cropland, is the highest in the nation (Pavelis, 1987). Accurate maps of preexisting tile lines are not only important for agronomic and environmental research but also for the maintenance and repair of current drainage systems, and for reference during the installation of new tile lines in previously tiled fields (Becker et al., 2021; Gökkaya et al., 2017; Tilahun & Syoum, 2021). In many cases, however, the locations of existing tile lines are not known exactly because maps of their locations were not made, the original maps have been lost, or the tile lines were inaccurately georeferenced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation